2019
DOI: 10.3390/microorganisms8010057
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Encapsulated Powder of Goji Berry (Lycium barbarum) on Growth and Survival of Probiotic Bacteria

Abstract: The aim of the present work was to investigate the potential prebiotic action of Goji berry powder on selected probiotic bacteria grown in a nutritive synthetic substrate and in simulated gastric and intestinal juices. Different probiotic strains of Bifidobacterium and Lactobacillus were grown in these substrates with or without the addition of encapsulated goji berry extracts of different polysaccharide and polyphenol contents. The results proved that the addition of the extracts promoted the proliferation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…Extracts of Genista tinctoria contributed to proliferation of probiotic strains and increased the number of bacterial colonies of Bifidobacterium animalis subsp. lactis, B. longum and Lactobacillus casei (Skenderidis & Giavasis, 2019). Prebiotic effect correlates with the concentration of polysaccharides and polyphenols of G. tinctoria, the content of which can increase the stress-tolerance of B. lactis and B. longum in a modelled gastrointestinal environment.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Extracts of Genista tinctoria contributed to proliferation of probiotic strains and increased the number of bacterial colonies of Bifidobacterium animalis subsp. lactis, B. longum and Lactobacillus casei (Skenderidis & Giavasis, 2019). Prebiotic effect correlates with the concentration of polysaccharides and polyphenols of G. tinctoria, the content of which can increase the stress-tolerance of B. lactis and B. longum in a modelled gastrointestinal environment.…”
Section: Discussionmentioning
confidence: 98%
“…Prebiotic effect correlates with the concentration of polysaccharides and polyphenols of G. tinctoria, the content of which can increase the stress-tolerance of B. lactis and B. longum in a modelled gastrointestinal environment. Skenderidis & Giavasis (2019) consider that encapsulated extracts from G. tinctoria could be used as prebiotic supplements for food products for stimulation of growth and increase in vitality of probiotic strains of Bifidobacterium and Lactobacillus.…”
Section: Discussionmentioning
confidence: 99%
“…These short-chain fatty acids produced by intestinal microbiota can be an energy source and decrease the luminal pH value, which is beneficial to the growth of probiotics and adverse to the growth of pathogens in the intestine [ 63 ]. An in vitro study found that LBP extract containing polysaccharides and polyphenols could be used as a source of food or nutraceuticals to help the growth of probiotics and protect the viability of Bifidobacterium and Lactobacillus in the simulated gastric and intestinal juices [ 64 ]. A previous study showed that LBP with major monosaccharides as glucuronic acid, galacturonic acid, glucose, galactose, and arabinose stimulated the production of short-chain fatty acids and increased the relative abundances of genera Bifidobacterium , Bacteroides , Phascolarctobacterium , Clostridium XlVb, Prevotella , and Collinsella in vitro after 24-h fermentation of LBP by healthy human fecal microbiota [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TPC was expressed as gallic acid (GA), and it was calculated by using a method described by Skenderidis et al [ 32 ]. Briefly, 1.58 mL distilled water was added in 0.02 mL of each extract.…”
Section: Methodsmentioning
confidence: 99%